2022
DOI: 10.2174/1389557521666210614162031
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Moiety: An Insight into Recent Advances in the Treatment of Cancer

Abstract: : The incidence of cancer is increasing worldwide, affecting a vast majority of the human population. As new different anticancer agents are being developed now, the requirement is to deal somehow with them and evaluate their safety. Among them, pyridine based drugs are contributing a lot, as it is one of the imperative pharmacophores occurring synthetically as well as naturally in heterocyclic compounds, and having a wide range of therapeutic applications in the area of drug discovery, thereby offering many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 115 publications
0
19
0
Order By: Relevance
“…In search for more effective benzoyl-phenoxy-acetamide (BPA) derivatives, we have decided to explore pyridine variants (Figure 2). This is because the pyridine moieties are part of a diverse group of compounds with broad pharmacological applications 33,34 . In addition, it is well documented that pyridine based compounds have a high probability to penetrate the CNS 35 .…”
Section: Resultsmentioning
confidence: 99%
“…In search for more effective benzoyl-phenoxy-acetamide (BPA) derivatives, we have decided to explore pyridine variants (Figure 2). This is because the pyridine moieties are part of a diverse group of compounds with broad pharmacological applications 33,34 . In addition, it is well documented that pyridine based compounds have a high probability to penetrate the CNS 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, researchers are currently focusing on the development of pyridine-based novel derivatives for cancer treatment. [4][5][6] Literature survey showed that different fused rings bearing pyridine moiety exhibited anticancer activity such as pyrano [3,2-c] pyridine, pyrido [4,3-d]-pyrimidine and pyrazolo [4,3-c] pyridine derivatives 13 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is the cause of about 30 percent of immediate deaths in adults aged 30 to 69 years due to non-communicable diseases. [1][2] Skin tumor is the most frequent type of malignancy with a total of 106,110 new melanomas diagnosed this year (about 62,260 in men and 43,850 in women), and melanoma is estimated to kill about 7,180 people. It occurs globally in all races, though the risk is significantly higher in Caucasians due to the photoprotective effect of epidermal melanin.…”
Section: Introductionmentioning
confidence: 99%